"The psychological impact of COVID-19 on medical education of final year students in Pakistan: A cross-sectional study". (December 2020) - Dhahri, Adeel Abbas; Arain, Sohail Yousuf; Memon, Ayesha Majeed; Rao, Ahsan; Mian, Muhammad Amer; ,; Khan, Muhammad M.; Hafeez, Gulzam; Dhahri, Mehvish A.; Mustafa, Faizan G.; Malhi, ShewaRam; Iqbal, Muhammad H.; et al.
Abstract: Introduction: COVID-19 pandemic has resulted in a strong impact on students' wellbeing, with associated uncertainty about the future. We conducted a cross-sectional survey to assess the psychological effects of COVID-19 on the medical education of final year students in Pakistan. Methods: We conducted prospective, cross-sectional survey, as a snapshot, from June 07, 2020 till June 16, 2020, among final year medical and dental students. The 20-questions survey questionnaire was based on rating-scale items to focus on psychological symptoms, institutional preparedness for such crisis and confidence in becoming a future doctor. Descriptive statistics were calculated using Multivariate regression analysis. Results: Majority of participants (n = 1753/2661, 65.9%) were female. Despite timely closure of institutes, delay in the start of the online teaching (beta coefficient 0.08, P-value 0.02) was significantly correlated with the depressive symptoms. A significant percentage of students (n = 1594, 59.9%) wanted a delay in exit exams due to intimidation. A similar proportion of students also lost confidence to be a competent doctor in future which was positively associated with male gender (beta coefficient 0.21, P-value < 0.001). Conclusion: Our study shows that COVID-19 pandemic has brought significant psychological influence on the medical education of final year students. Despite a stressful crisis, final year medical and dental students are still willing to serve the community. In addition to supporting their emotions and psychological wellbeing, stress counselling, and transforming current medical curricula is crucial to pursue ceaseless medical education and to become a safe future doctor. Highlights: COVID-19 pandemic has brought significant psychological influence on the medical education of final year students. A significant proportion of the medical and dental institutions were not well prepared before the lockdown. The students' preparation for their exams has been affected by the COVID-19 pandemic. Institutes need to establishing online 'social support group' with the mental health team to provide supportive therapy. Supporting students' emotions and psychological wellbeing, and transforming current medical curricula is crucial.